Liberal coercion? Prostitution, human trafficking and policy - Seo-young Cho (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
Liberal prostitution policy aims at improving labour conditions for prostitutes and protecting victims of forced prostitution. Its policy orientation predicts that the policy choice of liberalizing prostitution is positively associated with better protection policy for trafficking victims and enhanced anti-trafficking measures. In this paper, I investigate empirically whether the legalization of prostitution improves protection policy for victims, as it is presumed. The results of my analysis - using data from 149 countries for the period of 2001-2011 - suggest that the liberalisation of prostitution does not lead to better protection and, in some cases, legalized prostitution can be detrimental to protecting victims of human trafficking.
Keywords: J15; J16; K14; K37; 330; prostitution; victim protection; human trafficking; anti-trafficking policy